The crystal structure of cis-diaqua-bis (N-butyl-N-(pyridin-2-yl)pyridin-2-amine-κ2N,N′)cobalt(II)] dichloride trihydrate, C28H44Cl2N6O5Co - Alexander Orbett T.; Alberto Roger; Roodt Andreas (Zeitschrift für Kristallographie - New Crystal Structures)
C28H44Cl2N6O5Co, triclinic, P1‾$P‾{1}$ (no. 2), a = 11.20(2) Å, b = 12.70(3) Å, c = 12.80(4) Å, α = 100.30(12)°, β = 103.18(9)°, γ = 106.77(6)°, V = 1638(8) Å3, Z = 2, Rgt(F) = 0.0372, wRref(F2) = 0.0890, T = 100 K.